SPK PENENTUAN PRIORITAS PEMBANGUNAN INFRASTRUKTUR DESA MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS DAN WEIGHTED PRODUCT - Arif Setiawan; Eko Darmanto; Anis Maghfiroh (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
One important aspect in improving public services and community welfare is village infrastructure development. However, in Desa Piji, the process of determining development priorities has still been conducted manually through village deliberation meetings, making it vulnerable to subjectivity. This study aims to develop a Decision Support System (DSS) for determining village infrastructure development priorities using the Analytical Hierarchy Process (AHP) and Weighted Product (WP) methods. The AHP method was employed to determine the weight of each criterion through pairwise comparison matrices and consistency testing, while the WP method was used to calculate preference values and rank the development alternatives. The criteria used in this study include the level of infrastructure damage, the number of affected residents, development costs, and socio-economic impact. The consistency test results showed a Consistency Ratio (CR) value of 0.0389, which is less than 0.1, indicating that the criterion weights were consistent. The highest criterion weight was obtained for the level of infrastructure damage at 0.5117 (51.17%), followed by socio-economic impact at 0.2378, the number of affected residents at 0.1725, and development costs at 0.0780. From 21 processed development alternatives, alternative A019, namely the Construction of the KUD Block Drainage Channel, obtained the highest preference value of 0.056459244, making it the top priority. The developed system is capable of assisting the government of Desa Piji in determining infrastructure development priorities in a more objective, structured, and transparent manner.